2016
DOI: 10.1007/s12223-016-0475-6
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 and TLR21 expression, MIF, IFN-β, MD-2, CD14 activation, and sIgA production in chickens administered with EFAL41 strain challenged with Campylobacter jejuni

Abstract: The protective effect of Enterococcus faecium EFAL41 on chicken's caecum in relation to the TLR (TLR4 and TLR21) activation and production of luminal IgA challenged with Campylobacter jejuni CCM6191 was assessed. The activation of MIF, IFN-β, MD-2 and CD14 was followed-up after bacterial infection. Day-old chicks (40) were divided into four groups (n = 10): control (C), E. faecium AL41 (EFAL41), C. jejuni (CJ) and combined E. faecium AL41+C. jejuni (EFAL41+CJ). Relative mRNA expression of TLR4, TLR21 and CD14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Alternatively, A. mobilis and also, to some extent, L. reuteri CSF8 may have direct immunostimulatory properties, acting as vaccine adjuvants to enhance the antigen-specific immune response, an effect that was described previously for various vaccines in combination with Lactobacillus species in animal and human trials (51). Similar studies demonstrated that C. jejuni infection in combination with the administration of Enterococcus faecium probiotic strain AL41 resulted in the upregulation of Toll-like receptor 4 (TLR4)/MD2, which conferred responsiveness to bacterial lipopolysaccharide and to C. jejuni (52,53), enhanced migration inhibition factor (MIF) and beta interferon (IFN-␤) production, and prolonged activation of TLR21 compared to C. jejuni alone (53,54). In future studies, we also plan to examine the expressions levels of immunoglobulin and Toll-like receptors in bird serum samples by quantitative reverse transcription-PCR (qRT-PCR).…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively, A. mobilis and also, to some extent, L. reuteri CSF8 may have direct immunostimulatory properties, acting as vaccine adjuvants to enhance the antigen-specific immune response, an effect that was described previously for various vaccines in combination with Lactobacillus species in animal and human trials (51). Similar studies demonstrated that C. jejuni infection in combination with the administration of Enterococcus faecium probiotic strain AL41 resulted in the upregulation of Toll-like receptor 4 (TLR4)/MD2, which conferred responsiveness to bacterial lipopolysaccharide and to C. jejuni (52,53), enhanced migration inhibition factor (MIF) and beta interferon (IFN-␤) production, and prolonged activation of TLR21 compared to C. jejuni alone (53,54). In future studies, we also plan to examine the expressions levels of immunoglobulin and Toll-like receptors in bird serum samples by quantitative reverse transcription-PCR (qRT-PCR).…”
Section: Discussionmentioning
confidence: 85%
“…sIgA is an immune barrier that prevents toxins and intestinal pathogens from adhering to and penetrating the intestinal epithelium. sIgA inhibits allergens and pathogenic microorganisms and is the most important antibody for mucosal immunity in the body (Hodgkinson et al, 2017;Karaffová et al, 2017). In this study, sIgA content increased, indicating that the increase in sIgA content by two strains of Lactobacillus confers intestinal protection against pathogenic bacteria invasion.…”
Section: Discussionmentioning
confidence: 53%
“…88% ± 0.9 after Ent M application; so far this is even the highest stimulation of PA influenced by enterocins (33). Karaffová et al (24) reported modulation of TLR4, TLR21 expression and activation of MIF, IFN-β, MD-2 and CD14 in the caecum of chickens after oral administration of E. faecium AL41 to chickens and their infection with Campylobacter jejuni CCM6191. It could be stated that continuous preventive application of E. faecium AL41 during change of breeding or post hatching, for example, may stimulate the immune system of chickens.…”
Section: Discussionmentioning
confidence: 99%